Rare earth (RE – Ce, Gd) modified Nd1−xRExFeAsO0.7F0.3 superconductor with enhanced magneto-transport properties. Issue 52 (10th June 2015) - Aswathy, P. M.; Anooja, J. B.; Varghese, Neson; Chandrakanth, C. K.; Devendra Kumar, N.; Sundaresan, A.; Syamaprasad, U.
<x xml:space="preserve">Abstract</x> The influence of rare earth (RE – Ce, Gd) doping at the Nd site in the NdFeAsO0.7F0.3 superconductor wherein Ce and Gd have ionic radii in the order Ce > Nd > Gd is investigated.